Idiosyncratic liver injury induced by bolus combination treatment with emodin and 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside in rats - Li, Dan; Lyu, Yuanfeng; Song, Qianbo; Lai, Yuen Sze; Zuo, Zhong (Frontiers in Pharmacology, 2022)
Polygoni Multiflori Radix (PMR) is a commonly used traditional Chinese medicine in clinical practice, while adverse effects of hepatotoxicity related to PMR have been frequently reported. The clinical case reports indicated that PMR hepatotoxicity could occur under both overdose medication/long-term exposure and low doses with short-duration (idiosyncratic) conditions. The combination treatment with emodin and 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside (TSG), two major PMR components, was reported to contribute to PMR hepatotoxicity after long-term treatment. However, the role of the combination treatment of these two components in PMR-induced idiosyncratic liver injury has not been clearly clarified. In this study, the LPS-mediated inflammatory stress model rats were adopted to explore the idiosyncratic liver injury induced by the bolus combination treatment with emodin and TSG. After a bolus oral administration with TSG (165 mg/kg), emodin (5 mg/kg) or their combination in both normal and LPS-mediated inflammatory stress model rats, the systemic/hepatic concentrations of emodin, emodin glucuronides and bile acids were determined; the hepatotoxicity assessments were conducted via monitoring histopathological changes and liver injury biomarkers (ALT and AST). Moreover, the protein expressions of bile acid homeostasis- and apoptosis-related proteins were examined. No liver damage was observed in the normal rats after a bolus dose with the individual or combination treatment, while the bolus combination treatment with emodin and TSG induced liver injury in the LPS-mediated inflammatory stress model rats, evidenced by the elevated plasma levels of alanine aminotransferase ( 66%) and aspartate aminotransferase ( 72%) accompanied by severe inflammatory cell infiltration and apoptotic hepatocytes in liver tissue. Moreover, such combination treatment at a bolus dose in the LPS-mediated inflammatory stress model rats could significantly elevate the hepatic TBA levels by about 45% via up-regulating the hepatic protein expression levels of bile acid synthesis enzymes and inhibiting that of bile acid efflux transporters and the expression levels of apoptosis-related proteins. Our study for the first time proved the major contribution of the combination treatment with emodin and TSG in PMR-induced idiosyncratic liver injury.